การสังเคราะห์ส่วนของไดแอมิโนของโอเซลทามิเวียร์ - คณุตม์ ตั้งสง่าศักดิ์ศรี (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
The studies of the synthesis of the amino azide 8, which is part of the synthesis of oseltamivir, were carried out using epoxide 5 as the starting material. The key steps were the ring-opening of epoxide and aziridine. The previously reported 3-step synthesis was successfully reduced to just one step without any intermediates purifications, and gave the product 8 in 88 % yield. Moreover, the effect of solvent on the process was studied and found that the highest yield of amino azide 8 was obtained when using DMSO as the solvent. Furthermore, the phosphorus reagent was changed from phosphine to phosphite or phosphine-polymer bound and found that the precursor 6 progressed through the reaction, but could not reach the targeted product. Additionally, the attempt to apply this reaction on styrene oxide could convert the reactant along the reaction path. However, the expected product was yet unable to be isolated.